Personal Factors of Communicative Competence of Future Pilots - Vasheka, Tetiana; Dolgova , Olena; Vlasova-Chmeruk, Oksana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article considers the problem of communicative competence of future pilots and establishes its personal factors. The urgency of the chosen issue is due to the significant contribution of the human factor, including ineffective communication, in the occurrence of aviation incidents and accidents. The purpose of the study was to establish the level of communicative competence and its personal factors in students majoring in "Aviation". The obtained results allowed us to perform correlation analysis using SPSS software package. With the help of L Michelson’s Test of Communication Skills and the Methodology for Assessing the Level of Communicative and Organizational Abilities of V Sinyavsky and B Fedoryshyn, it was established that most respondents have well-developed communication skills, but 20% were diagnosed with low level. Correlation analysis of communication indicators and personality traits (FPI test) showed a direct relationship between communicative competence and sociability and balance, and the reverse - with neuroticism, depression, reactive aggression, shyness and emotional lability. Extraversion and masculinity are associated with the expressed communicative abilities of future pilots. The most important personal factors in the communicative competence of future pilots are the low level of dependence in communication and reactive aggression, and the communicative abilities - the low level of shyness and depression. The obtained results confirm the assumptions about the insufficient formation of communicative competence of future pilots and indicate the need for the formation and development of skills of effective communication in the learning process.